Optimization of aqueous extraction condition of total phenolic compound from the leaves of Sirih Hijau (Piper betle L.) - Raja Muhammad Farid Raja Semail (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Green betel (Piper betle L.) has long been regarded as food and well known for its medicinal properties. Experiment has been done to obtain total phenolic compounds of green betel leaves extract and antioxidant activity from the extracts has been observed. Several experiment conducted to determine parameters for optimization of extraction condition using Response Surface Methodology (RSM) in conjunction with central composite design (CCD). The range of the independent variables, namely as extraction time (60-120 minutes) and extraction temperature (85-100 oC) were determined by a preliminary study of single factor parameter, then the values of independent variables were selected based on results of preliminary study. The optimum condition for green betel leaf was found to be at extraction time of 104.10 minutes and extraction temperature of 88.73 oC. Under these optimized condition, the maximum yield of TPC was 613.50 mg GAE/ 100 g DW which indicates that the suitability of the models developed and the success of RSM in optimizing the extraction condition.